Analisis Kesalahan Berbahasa Indonesia Mahasiswa Terhadap Dosen Melalui Media WhatsApp Oleh Mahasiswa Biologi UNIMED - Hadyan Wafi Nahdah; Priska Amanda; Alya Anugrah Siregar; Nitya Ilmi Hasibuan; Lili Tansliova (Universitas Maritim AMNI Semarang, 2024)
This study focused on UNIMED Biology Department students and aimed to find Indonesian language errors in their WhatsApp conversations with lecturers. The data included messages sent by UNIMED biology students to lecturers via WhatsApp. A qualitative analysis was conducted to compare this data with language error standards set in good and correct Indonesian language rules, such as EYD, PUEBI, and KBBI. The results showed that some of the language mistakes that often occur in conversation include incorrect word use, incorrect punctuation, and ineffective sentences